Application of semi-analytical finite element method to evaluate asphalt pavement bearing capacity. Issue Volume 19:Issued 6(2018) (3rd June 2018) - Liu, Pengfei; Wang, Dawei; Otto, Frédéric; Hu, Jing; Oeser, Markus
Abstract: Bearing capacity is a key index in pavement management systems in many countries, which reflects the essential material properties of asphalt pavements. Many stationary measuring methods have been undertaken in the past; current assessment of the bearing capacity tends towards fast and continuous measurements at traffic speed for a network analysis. The conventional evaluation using stationary loads do not represent real traffic loading condition; therefore the results will inevitably lead to discrepancies from reality. A specific computational program SAFEM based on semi-analytical finite element method is proposed to overcome the difficulty. The reliability and efficiency of the SAFEM is proved by verification with commercial FE software ABAQUS and field measurements. The variation tendency of the back-calculated bearing capacity has a quite good negative linear relation with the number of loading cycles in the experiment. The investigation shows this proposed assessment system is a feasible option for the fast and reliable analysis of the pavement bearing capacity at a network level for road administrations.